Theology from the Psalms: the story of God's steadfast love - Bullock, C. Hassell (Baker Academic, 2023)
Intro -- Endorsements -- Half Title Page -- Title Page -- Copyright Page -- Dedication -- Contents -- Preface -- Introductory Matters -- Part 1: God -- 1. The Aleph and Tav of Psalmic Theology -- 2. Hesed, God's Steadfast Love -- 3. Thinking Comprehensively about God's Goodness (Tob) -- 4. Yahweh's Condescension in the Psalter -- 5. Judgment, the Other Side of Justice -- 6. Covenant, the Intractable Bond -- 7. The Laughter of God -- Part 2: Humanity -- 8. The Human Condition -- 9. We Become Like Our God -- 10. Shamed and Shaming -- 11. Weeping for the Night, but Joy in the Morning -- 12. Waiting on the Lord -- 13. They Did Not Remember to Show Kindness -- Part 3: Redemption -- 14. All in the Family: "For His Name's Sake" -- 15. Finding God in the Fabric of the World -- 16. The Fear of the Lord -- 17. Praise of God, the Rehearsal Hall for Eternity -- Bibliography -- Scripture Index -- Subject Index -- Back Cover.